Laparoscopic repair of irreducible femoral hernia containing the fallopian tube alone: a case report - Soeta, Nobutoshi (Surg Case Rep, 2016)
BACKGROUND: We offer the first report of laparoscopic repair of an irreducible femoral hernia containing the fallopian tube alone. CASE PRESENTATION: An 84-year-old woman presented with a 2-week history of a right groin mass with no abdominal symptoms. The mass was located below the inguinal ligament but showed no redness or tenderness. Abdominal computed tomography demonstrated a 4 × 3-cm cystic mass and enhanced cord-like structure in the right groin area. Hernia contents were considered potentially associated with the appendix, and right femoral hernia incarceration was diagnosed. We performed emergency surgery using a laparoscopic approach, revealing an irreducible femoral hernia containing the right fallopian tube, which was reduced laparoscopically. The reduced fallopian tube showed no ischemic changes, obviating the need for resection. No other abdominal organs such as the ovary, fimbriae of the fallopian tube, or appendix were incarcerated. We repaired the femoral hernia laparoscopically using a transabdominal preperitoneal approach with a mesh. CONCLUSIONS: A laparoscopic approach offers ready and accurate confirmation of incarcerated or irreducible organs, rapid recovery, and favorable cosmesis and should therefore be considered for the treatment of incarcerated or irreducible femoral hernia.